Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/wics.6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of outliers

Abstract: We present an overview of the major developments in the area of detection of outliers. These include projection pursuit approaches as well as Mahalanobis distance-based procedures. We also discuss principal component-based methods, since these are most applicable to the large datasets that have become more prevalent in recent years. The major algorithms within each category are briefly discussed, together with current challenges and possible directions of future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(73 citation statements)
references
References 62 publications
0
65
0
3
Order By: Relevance
“…The term `outlier' refers to values of the response variables which are unusually large or small [3,7]. Since all of the explanatory variables in our case are factors, any abnormal values are likely to be outliers.…”
Section: Methodsmentioning
confidence: 99%
“…The term `outlier' refers to values of the response variables which are unusually large or small [3,7]. Since all of the explanatory variables in our case are factors, any abnormal values are likely to be outliers.…”
Section: Methodsmentioning
confidence: 99%
“…Various methods for identifying outliers have been proposed based on di↵erent methodologies, like statistical reasoning (Hadi et al (2009)), distances (Angiulli and Pizzuti (2002); Knorr et al (2000);and Orair et al (2010)), or densities (Breunig et al (2000)); (De Vries et al (2010) and Keller et al (2012)). But the issue is not completely solved, and in some methodologies, such as causal inference, this issue may become crucial.…”
Section: A Brief Review Of the Literaturementioning
confidence: 99%
“…Here, swamping means a true positive becomes a false negative, while masking means a true negative becomes a false positive. These two terminologies are often used for outlier detection (Ben-Gal 2005;Hadi et al 2009): swamping means some non-outliers are identified as outliers, while masking means some outliers are not identified; outliers mask themselves by swamping some non-outliers. We borrow them here to characterize the two results of (P1) (P2) in MB discovery because of their similar behaviors in "masking" themselves and "swamping" others.…”
Section: Introductionmentioning
confidence: 99%